2013
DOI: 10.1016/j.ijsu.2013.06.843
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the 3-D finite element solid model of femurs in partial by volume rendering

Abstract: Compared with whole modeling by volume rendering method, the 3-D finite element solid model created in partial is more real and fit for finite element analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The initial cylindrical volume has a Young's modulus of 1 MPa. Poisson's ratio is 0.3 for all modeled materials (Wang et al, ; Zhang et al, ). The model is meshed by 674,431 eight node tetrahedral solid elements (SOLID185) assuming an element size of 0.6 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The initial cylindrical volume has a Young's modulus of 1 MPa. Poisson's ratio is 0.3 for all modeled materials (Wang et al, ; Zhang et al, ). The model is meshed by 674,431 eight node tetrahedral solid elements (SOLID185) assuming an element size of 0.6 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The three types of bone trabeculae increase the rigidity of the passing area by 160 to 400%. Zhang Y found that the compression forces were mainly concentrated on the medial surface of the femur by a finite element analysis [10]. The anterior wall of the femur at the calcar's level is strong and thick but the posterior wall is otherwise.…”
Section: Main Textmentioning
confidence: 99%
“…CT imaging enables the creation of complex models that can be subsequently used for finite element analysis simulations. 7 , 34 , 35 …”
Section: Introductionmentioning
confidence: 99%
“…CT imaging enables the creation of complex models that can be subsequently used for finite element analysis simulations. 7,34,35 It is well known that the femoral neck is a site of complex loading, shared between cortical and trabecular compartments, and pre-existing osteoporosis further increases the risk of a femoral neck fracture after falls. Within the proximal femur, the trabecular system provides a specific distribution that allows it to support the body's weight.…”
Section: Introductionmentioning
confidence: 99%